Rapid identification of Enterobacteriaceae with the micro-ID system versus API 20E and conventional media. - Barry, A L (1979)
The Micro-ID system for rapid (4 h) identification of Enterobacteriaceae was evaluated by testing 433 enteric bacilli and 9 other gram-negative bacilli. Each isolate was identified with conventional tubed media and was also tested in the Micro-ID and API 20E systems. The overall accuracy of both systems was 97%. Micro-ID tests for the Voges-Proskauer reaction, indole and H2S production, and ornithine and lysine decarboxylase all demonstrated a 97 to 99% correlation with conventional methods. Only 86% of the Micro-ID urease tests agreed with Christenson urea agar. Two inoculum densities were tested in Micro-ID panels, with 157 stock cultures. Over 90% of the tests were unaffected by changes in inoculum density. Tests with four control strains suggested that the Micro-ID system was more reproducible when a light inoculum was used. The Micro-ID system was found to be a very convenient method for rapid, accurate, and precise identification of the Enterobacteriaceae.